Characterization of intra-tumoral microbiota from transcriptomic sequencing of Asian breast cancer - Yeo, Li-Fang; Lee; Audrey Weng Yan; Tee; Phoebe Yon Ern; Chin; Joyce Seow Fong; Lee, Bernard K. B.; Lim, Joanna; Teo, Soo-Hwang; Pan, Jia-Wern (Springer Nature, 2026)
The human microbiome has garnered significant interest in recent years as an important driver of human health and disease. Likewise, it has been suggested that the intra-tumoral microbiome may be associated with specific features of cancer such as tumour progression and metastasis. However, additional research is needed to validate these findings in diverse populations. In this study, we characterized the intra-tumoral microbiota of 883 Malaysian breast cancer patients using transcriptomic data from bulk tumours and investigated their association with clinical variables and immune scores. We found that the tumour microbiome was not associated with breast cancer molecular subtype, cancer stage, tumour grade, or patient age, but was weakly associated with immune scores. We also found that the tumour microbiome was associated with immune scores in our cohort using random forest models, suggesting the possibility of an interaction between the tumour microbiome and the tumour immune microenvironment in Asian breast cancer.